Estimasi Kedalaman Bitumen Batubara di Desa Banjaran Kecamatan Salem Kabupaten Brebes Berdasarkan Data Anomali Magnetik - Sehah S; Sukmaji Anom Raharjo; Adi Chandra (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2017)
The Estimation of coal bituminous depth in Village of Banjaran, District of Salem, Regency of Brebes based on magnetic anomaly data has been done. The Village of Banjaran is located in the geology basin which called as Bentarsari Basin. The activities stages that carried out in this research include of magnetic data acquisition in the field, data processing, and interpretation. The interpretation of the anomalies data is done through the modeling using the Mag2DC for Window software on the local magnetic anomalies data. Based on this modeling results, then obtained six anomalous objects that can be interpreted as the subsurface rocks in the research area, which consists of sediments of gravel, sand, clay, and silt ( = 0.0020 cgs units); tuff and tuffaceous sandstone ( = 0.0069cgs units); andesite breccia, tuff, and tuffaceous sandstone ( = 0.0085cgs units); solid andesite breccia which not layered ( = 0.0115 cgs units); coarse sandstones, limestones, and sandy marl ( = 0.0109cgs units); andesite sandstone that layered with claystone and thin insertions of new coal bituminous alternately ( = 0.0008cgs units). Based on the modeling results and the geological information of this research area, it can be estimated that the coal bituminous found in the Kaliglagah formation, with its depths ranging between 104.48 m – 505.97m, and the value of the magnetic susceptibility is 0.0008 cgs units.